Comparison of hearing outcomes after treatment for early‐stage external auditory canal cancer. (7th October 2015) - Morita, Shinya; Nakamaru, Yuji; Homma, Akihiro; Sakashita, Tomohiro; Hatakeyama, Hiromitsu; Masuya, Masayori; Fukuda, Satoshi
Abstract: Background: The purpose of this study was to compare the hearing outcomes after surgery with reconstruction of the external auditory canal in combination with tympanoplasty, radiotherapy (RT) alone, and surgery followed by postoperative RT for T1 to 2N0M0 external auditory canal cancer. Methods: We performed a retrospective, single‐institution review of consecutive patients with early‐stage external auditory canal cancer treated with surgery and/or RT between April 1997 and August 2013. Audiological data included the pretreatment hearing thresholds and those obtained at 12 months after the completion of therapy. Results: When we compared the functional gains for air‐conduction pure‐tone average thresholds and mean air‐bone gaps, those in the surgery group ( n = 10) were significantly higher than those in the RT ( n = 13) and surgery + RT ( n = 5) groups. Conclusion: Adequate techniques for reconstruction of the external auditory canal in combination with tympanoplasty after complete surgical resection is useful for hearing preservation in addition to good survival outcomes. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1110–E1116, 2016